Hardware development on auto focuse microscope - Muhammad Hafizuddin, Basri (2016)
The scientific instrument technology has growth faster than we all could imagine, there are many research team keeping their momentum in creating new innovation in scientific instrumentation technologies. The optical microscopes are still being used widely in the scientific research especially by researcher and medical practitioners. Manually deal with the microscope could make the user spend so much time to obtain the result of cleared image. It could cost hours to obtain the desire result. From this problem, the author would like to introduce a hardware system for auto focused of optical microscope. There consist of two stepper motor that will be function to control the fine focus knob and the course focus knob. The timing belts are being used as mounting between the stepper motor and the fine/course focus knob. The motor will moves step by step in same degree given from the command of programming. The motor are able to be control and it move slowly and in able to move in a small angle to finding the exact proper exposure of the images scan. The hardware implementation of auto focus on the optical microscope has been tested and it work perfectly.